NUMERICAL INVESTIGATION OF STATIC AND DYNAMIC STRESSES IN SPUR GEAR MADE OF COMPOSITE MATERIAL (Journal of Engineering, 2011)
In this current work, Purpose; to clearly the fundamental idea for constructing a design andinvestigation of spur gear made of composite material its comes from the combination of (highspeeds, low noise, oil-les running, light weight, high strength, and more load capability)encountered in modern engineering applications of the gear drives, when the usual metallic gearcannot too overwhelming these combinations.An analyzing of stresses and deformation under static and dynamic loading for spur gear toothby finite element method with isoparametric eight-nodded in total of 200 brick element with 340nods in three degree of freedom per node was selected for this analysis. This is responsible for thecatastropic failure studying of spur gear made of composite material. Also obtain the naturalfrequencies and the mode shape of the composite tooth under (concentrated and or moving onsurface profile) load of one half sinusoidal type impulse for two types of composite materials(Glasses/Epoxy & Graphite/Epoxy) and they are compared with the mild steel gear values.The appearances that improve the successfully of composite gear in the weight, stiffness, loadcapability, and dynamic behavior respect to the mild steel, which is found that composite materialsmay also be thought of as a material for power transmission gearing, from a stress point of view.